Мотив безсмертя у романістиці Леоніда Горлача - Федько, Ольга Юріївна; Fed’ko, Olha; Fedko, O. (My University, 2021)
STRESZCZENIE. Artykuł został poświęcony analizie funkcjonowania motywu nieśmiertelności w powieściach poetyckich Leonida Horłacza (Mamaj, Ruina, Czyste pole, Palec Askolda, Wyspa Słowiańska). Na podstawie prac P. Bargara, A. Wesełowskiego, І. Dziuby, J. Morgana, І. Sylantiewa, S. Thompsona przedstawiono osobliwości motywu jako formuły literackiej. Trafność badania wynika z mitologicznego korzenia inwariantnego motywu nieśmiertelności, jego wyjątkowej roli w kulturze ukraińskiej (i w ogóle światowej) i omijania tego tematu w studiach nad utworami L. Horłacza. Naświetlono wykorzystanie przez pisarza pogańskich i chrześcijańskich tradycji opisu życia po śmierci, potraktowanie nieśmiertelności jako cechy bóstwa albo nagrody i kary dla ludzi. Motyw nieśmiertelności jest również związany z pamięcią, sławą i wkładem osobistości we wspólne dzieło. Realizacji analizowanego motywu sprzyjają mitologemy, symbole i alegorie (nić Mojr, ogień, sad, pszczoła). ABSTRACT. The article deals with the analysis of functioning of the immortality motif in L. Horlach’s poetic novels (Mamay, Ruin, Open Field, Askold’s Finger, Slavic Island). Based on the works of P. Bargar, A. Veselovskij, I. Dziuba, J. Morgan, I. Silantev and S. Thompson, the scecific nature of the motif as a literary element is presented. The relevance of the study is determined by the mythological origin of the invariant motif of immortality, its unique role in Ukrainian (and world-wide) culture and the lack of studies on this topic, all based on L. Horlach’s works. This paper shows the writer’s use of pagan and Christian traditions in describing the afterlife, the understanding of immortality as a feature of a deity or as a reward and punishment for people. The motif of immortality is also connected to the concept of memory, fame and the contribution of personalities to the common goal. The motif is analyzed using mythologies, symbols and allegories (the thread of Moirai, fire, garden, bee).
Motyw nieśmiertelności w powieściach Leonida Horłacza
The motif of immortality in Leonid Horlach’s novels
ORCID: 0000-0002-2993-9471
Keywords: powieść poetycka; motyw; nieśmiertelność; symbol; mitologem; verse novel; motif; immortality; symbol; mythologem